High Blood Flow Into the Femur Indicates Elevated Aerobic Capacity in Synapsids Since the Synapsida-Sauropsida Split - Knaus, Philipp L.; van Heteren, Anneke H.; Lungmus, Jacqueline K.; Sander, P. Martin (Frontiers in Ecology and Evolution, 2021)
Varanids are the only non-avian sauropsids that are known to approach the warm-blooded mammals in stamina. Furthermore, a much higher maximum metabolic rate (MMR) gives endotherms (including birds) higher stamina than crocodiles, turtles, and non-varanid lepidosaurs. This has led researchers to hypothesize that mammalian endothermy evolved as a second step after the acquisition of elevated MMR in non-mammalian therapsids from a plesiomorphic state of low metabolic rates. In recent amniotes MMR correlates with the index of blood flow into the femur (Qi), which is calculated from femoral length and the cross-sectional area of the nutrient foramen. Thus, Qi may serve as an indicator of MMR range in extinct animals. Using the Qi-proxy and phylogenetic eigenvector maps, here we show that elevated MMRs evolved near the base of Synapsida. Non-mammalian synapsids, including caseids, edaphosaurids, sphenacodontids, dicynodonts, gorgonopsids, and non-mammalian cynodonts, show Qi values in the range of recent endotherms and varanids, suggesting that raised MMRs either evolved in synapsids shortly after the Synapsida-Sauropsida split in the Mississippian or that the low MMR of lepidosaurs and turtles is apomorphic, as has been postulated for crocodiles.